Effects of coffee management on Bee Floral Diversity, Honey Yield and Quality: The Case of Gera District, Jimma Zone, South West Ethiopia - Shabu Jemal Abakorma; Kitessa Hundera; Zerehun Kebebew (Universitas Prof. Dr. Hazairin SH, 2020)
This study was conducted to assess the effect of forest management for coffee cultivation on bee flora diversity, honey yield and quality as forest crop products in Gera district. Forest coffee (FC) and Semi-forest coffee (SFC) plots were selected for bee flora assessment. Total of 34 plots (FC = 17, SFC = 17) with plot size 20 m x 20 m (400 m2) were assessed. Sixty bee flora species belonging to trees (30), shrubs (21) and woody lianas (9) were identified and compared across plots. Results show that more bee flora diversity in FC (2.03) than SFC (1.09) system. Honey yield data was collected from 78 (FC = 52, SFC = 26) beekeepers. The honey yield of FC was higher than SFC system in both high and low production years. The honey production on average was 9.58 kg hive-1 for FC and 6.44 kg hive-1 for SFC in high production year while 6.5 kg hive-1 for FC and 4.24 kg hive-1 for SFC in low production year. To assess the honey quality, 6 kg honey samples (FC = 3, SFC = 3) were collected. Six honey quality parameters i.e. moisture, ash, pH, free acidity, electrical conductivity (EC) and total soluble solid (TSS) contents. The biochemical variation in the composition is significantly different (P<0.05) in ash content, pH, EC and free acidity when comparing FC with SFC honey samples while the percentage of moisture and TSS contents were insignificant (p>0.05). The study revealed that coffee management is associated with a decline in bee flora diversity, honey yields and on top of this, it has implications on honey quality deteriorations. Thus, there is an urgent need for control and monitoring on the expansion of SFC cultivation, which needs immediate conservation measures. Therefore, conservationists have to take actions for biodiversity conservation specially bee flora species diversity and ecosystem services that accompanied with coffee management and FC intensifications.